Pentingnya Pengaturan Hukum Bagi Suporter dalam Menyikapi Problematika Turnamen Sepak Bola Antar Kampung di Kabupaten Flores Timur - Wolo, Hironimus Bao; Aran, Kristoforus Ado (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The problem of this research is that one of the causes of anarchic actions by supporters is not being ready to accept their team’s defeat. The purpose of this study is to identify football supporters who act anarchically and offer a solution regarding the importance of legal regulations for supporters in responding to the problems of inter-village football tournaments in East Flores Regency. The research method used is normative legal research with a legal political approach. The research results show that: 1) there were several anarchic actions by supporters in the football tournament held in East Flores Regency, including Sora Lamawalang FC (July 30, 2022), Arsenal Terong supporters vs Bon Kota Fc supporters (August 6, 2022), Persela Lamahala supporters vs Citra Damai supporters (August 25, 2022), Bunga Baru supporters (June 2022), Perseftim supporters (September 23, 2023), and Citra Damai supporters vs Janur Waiwerang supporters (November 6, 2023); 2) the national legal basis for the formation of normative regulations: Undang-Undang Nomor 11 Tahun 2022 tentang Keolahragaan and Kode Disiplin PSSI 2023. These regulations should guarantee and enforce the rules for fans who act anarchically at inter-village football events in East Flores. These regulations contain a) sanctions for supporters and their support teams; b) cooperation between the implementing committee and the support coordinator and public authorities, for example, the police; c) the obligation to map the risk of security disturbances; and d) the obligation to ensure the safety of supporters and spectators during and after the match.